Reflectarray antennas - Huang, John (IEEE Press Wiley-Interscience, 2018)
Describes the configuration and principles of a reflectarray antenna, its advantages over other antennas, the history of its development, analysis techniques, practical design procedures, bandwidth issues and wideband techniques, as well as applications and recent developments. Both authors are well respected practitioners who have build these antennas and developed them for space flight